2015
DOI: 10.1016/j.neo.2015.04.004
|View full text |Cite
|
Sign up to set email alerts
|

Hematopoietic Stem Cell–Derived Cancer–Associated Fibroblasts Are Novel Contributors to the Pro-Tumorigenic Microenvironment

Abstract: Targeting the tumor microenvironment is critical toward improving the effectiveness of cancer therapeutics. Cancer-associated fibroblasts (CAFs) are one of the most abundant cell types of the tumor microenvironment, playing an important role in tumor progression. Multiple origins for CAFs have been proposed including resident fibroblasts, adipocytes, and bone marrow. Our laboratory previously identified a novel hematopoietic stem cell (HSC) origin for CAFs; however, the functional roles of HSC-derived CAFs (HS… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
39
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(41 citation statements)
references
References 67 publications
1
39
0
1
Order By: Relevance
“…The source of CAFs varies strongly and often according to tumor type. Stellate cells, bone-marrow-derived mesenchymal stem cells, mesenchymal stem cells from adipose tissue, and resident quiescent fibroblasts have been identified as cells of origin for CAFs (McDonald et al, 2015;Barcellos-de-Souza et al, 2016;Borriello et al, 2017;Ohlund et al, 2017). Not surprisingly, given their varying origin, CAFs are a heterogeneous cell population that can have strong differences in morphology, cell-cell interaction, and expression profile.…”
Section: Carcinoma-associated Fibroblastsmentioning
confidence: 99%
“…The source of CAFs varies strongly and often according to tumor type. Stellate cells, bone-marrow-derived mesenchymal stem cells, mesenchymal stem cells from adipose tissue, and resident quiescent fibroblasts have been identified as cells of origin for CAFs (McDonald et al, 2015;Barcellos-de-Souza et al, 2016;Borriello et al, 2017;Ohlund et al, 2017). Not surprisingly, given their varying origin, CAFs are a heterogeneous cell population that can have strong differences in morphology, cell-cell interaction, and expression profile.…”
Section: Carcinoma-associated Fibroblastsmentioning
confidence: 99%
“…While a majority of CAFs are thought to arise from activation of resident fibroblasts (see below), studies in genetically modified mouse models have demonstrated that about one-third of CAFs derive from other sources: bone marrow (BM)-derived cells (Quante et al 2011;Lecomte et al 2012;McDonald et al 2015), adipocytes (Bochet et al 2013), endothelial cells (Zeisberg et al 2007), or even, perhaps, epithelial cells (Radisky et al 2007) that undergo mesenchymal transition when instructed by systemic factors secreted by the tumor (Chen et al 2015a). This complexity has led some investigators to propose that a CAF is a "cell state" rather than a "cell type" (Madar et al 2013).…”
Section: Caf: Cell or State?mentioning
confidence: 99%
“…Besides PSCs, there is evidence that PDAC CAFs can also arise from mesenchymal stem cells (MSCs), bone marrow-derived stem cells, and/or endothelial cells ( Figure 1A) [36][37][38]. In other solid tumours, there is evidence to suggest that CAFs also derive from local resident fibroblasts [39], adipocytes [40], adipose-derived MSCs [41,42], hematopoietic stem cells [43], and pericytes [44]. However, most of these studies were performed using cell culture or transplantation approaches, highlighting the lack of lineage-tracing studies that adequately address the origin of CAFs (see Outstanding uestions).…”
Section: Heterogeneity Of Caf Biomarkersmentioning
confidence: 99%